PENGARUH DISIPLIN KERJA, KOMITMEN ORGANISASI DAN PELATIHAN TERHADAP KINERJA YANG BERDAMPAK KEPADA PRESTASI KERJA - Sukowati Sukowati; Afrizal Afrizal; Wargianto Wargianto (JEM Jurnal Ekonomi dan Manajemen, 2018)
This research is based on several variables that can affect the performance and achievement of teachers in SMA Negeri 1 Kelapa. After conducting a field survey, the authors finally determined some variables that could affect the performance as well as job performance in SMA Negeri 1 Kelapa, ie work discipline, organizational commitment and training This study aims to examine the discipline of work, organizational commitment and training on performance that impact teacher work performance in SMA Negeri 1 Kelapa. Methods in this study using survey methods and questionnaires to all respondents who numbered 42 people. This research uses quantitative analysis to primary data on field survey results. The result of this research is known that, firstly, the influence of simultaneously variable of work discipline, organizational commitment and training on teacher performance. Second, the partial influence of work discipline variables on performance. Third, the partial influence of organizational commitment variable on performance. Fourth, the partial influence of training variable on performance. Fifth, the partial influence of performance variable on work performance